Monstrous Births and Imaginations: Authorship and Folklore in Shakespeare’s A Midsummer Night’s Dream - Walters, Lisa (Renaissance and Reformation / Renaissance et Réforme, 2016)
The amateur actors in A Midsummer Night’s Dream are compared several times with the fairies who inhabit a forest outside of Athens. This article will investigate the significance of the analogy by exploring commonalities between discursive elements in folklore, physiology, and philosophy that regard imaginative faculties as a powerful force. When contextualizing Shakespeare’s representation of acting and writing within early modern assumptions about the nature of the imagination and its relation to popular stories of monstrous births, fairies, and witches, we can see that A Midsummer Night’s Dream portrays theatre as a medium containing subversive political and erotic energies that potentially can alter the socio-political landscape.